Diagnóstico y establecimiento de La Red Hidrométrica menor del Sector Hidraulico Yamobamba - Chusgón - margen izquierda del Rio Marañón - La Libertad. 2017 - Acuña Fernandez, Fermin (2017)
The present study aims to perform the DIAGNOSIS AND ESTABLISH THE HYDROOMETRIC NETWORK OF THE HYDRAULIC SECTOR YAMOBAMBA-CHUSGÓN - LEFT MARGIN OF THE RIO MARAÑÓN - LA LIBERTAD. 2017. which consists of three stages of studies. The first part of the study includes a general description of the scope of the study and the diagnosis of the socioeconomic, environmental, soil, geology and surface water resources aspects and hydraulic infrastructure in the Hydraulic Sector, consisting of sixteen (16) hydraulic subsectors , for which we had field material, a map of the delineation of the hydraulic subsectors, provided by the ALA and the Users Board of the Yamobamba -Chusgón Hydraulic Sector - Left Margin of the Marañón River Then, the work plan was established, in coordination with the Manager of the Users' Board, Commissions Commissions and Users Committees of the Hydraulic Sector. Once the work plan for field evaluation and diagnosis was established, each one of the hydraulic subsectors was run, with the assistance of the managers and watchmen and / or managers responsible for the distribution of water. According to the established methodology and the information to be collected in the field (Format Nº 01), it consisted in the location of bocatomas or pickings; places where new measurement structures are proposed; for this a Garmin GPS was used